(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Anticonvulsants drugs are a diverse group of pharmacological agents used in the treatment of epileptic seizures are known to inhibit or activate cytochrome p-450 enzymes that play a crucial rule in the metabolic process. Objective:To investigate any possible differences in the effect of antiepileptic drugs; enzyme inducer (carbamazepine) and enzyme inhibitor (lamotrigine) on lipid profile in normal and diabetic rabbits depending on its effect on cytochrome p-450 enzymes. Methods:Fifty four healthy domestic rabbits of both sexes weighing 0.5-2.5 kg were studied. They were divided into group A (standard) received tolamatrigine and carbamazepine without induction of diabetes and group B (received the same regimen) with induction of diabetes. Lipid profile was tested in the two groups. Results: Carbamazepine-treated group showed a significant increase in the lipid profile at day 20 of treatment compared to day 5 in comparison with induced and non-induced control groups and control group in normal and diabetic rabbits. Lamotrigine showed less effect on lipid profile; and in non-diabetic treated groups it showed a non-significant change in lipids level as compared to the control group. Conclusions:Anti-epileptics drugs that possess an enzyme inducing effect as carbamezpin tend to induce high lipids profile in comparison to lamotigine. Keyword: Lamotrigine, carbamazepine, anticonvulsants, glucose, lipid.